Microwave Assisted Synthesis, Spectral and Antifungal Studies of 2-Phenyl-N,N′-bis(pyridin-4-ylcarbonyl)butanediamide Ligand and Its Metal Complexes - Rayees Ahmad Shiekh; Maqsood Ahmad Malik; Shaeel Ahmed Al-Thabaiti; Mohmmad Younus Wani; Arshid Nabi (The Scientific World Journal)
2-Phenyl-N,N′-bis(pyridin-4-ylcarbonyl)butanediamide ligand with a series of transition metal complexes has been synthesized via two routes: microwave irradiation and conventional heating method. Microwave irritation method happened to be the efficient and versatile route for the synthesis of these metal complexes. These complexes were found to have the general composition M(L)Cl2/M(L)(CH3COO)2 (where M = Cu(II), Co(II), Ni(II), and L = ligand). Different physical and spectroscopic techniques were used to investigate the structural features of the synthesized compounds, which supported an octahedral geometry for these complexes. In vitro antifungal activity of the ligand and its metal complexes revealed that the metal complexes are highly active compared to the standard drug. Metal complexes showed enhanced activity compared to the ligand, which is an important step towards the designing of antifungal drug candidates.